Middle‐aged individuals' sexual risk‐taking: Analysis of Swedish research and prevention policies. Issue 1 (27th June 2019) - Lundström, Mats; Ouis, Pernilla
Abstract: This article critically examines the basis for Swedish prevention strategies and policy documents concerning sexual risk‐taking, investigating in particular how risk‐taking is represented with respect to the group of middle‐aged, heterosexual individuals. These prevention strategies and policy documents seem to be built on an assumption that sexual relationships are limited to people having sex with individuals with the same sexual orientation, age, behaviour or drug use, an assumption that can be questioned. We have made a scoping review of existing research and examined Swedish national prevention strategies, analysing policy documents on sexual risk‐taking. The results demonstrate a lack of both research and interventions targeted at middle‐aged heterosexuals. We argue that research and interventions directed to heterosexuals have strong connections to fertility. Drawing on Loseke's theorization, the explanation might be that middle‐age sexual behaviour loses the "social problem game". The blind spots observed in research and policy can also be explained by an agreement in normativity between the different claims‐makers, such as interest groups, policy‐makers and politicians. 摘要: 本文批判地检验了有关性冒险的瑞典预防策略和政策文件，尤其调查了性冒险在中年异性恋人群中的体现形式。这些预防策略和政策文件看似建立于一种假设，即性关系仅存在于那些与拥有相同性取向、年龄、行为或使用药物的个人发生性关系的人群。该假设存在被质疑的可能。笔者对现有文献进行了范围综述 (scoping review), 同时检验了瑞典国家预防策略，分析了有关性冒险的政策文件。研究结果显示，针对中年异性恋人群的研究和干预措施还很缺乏。笔者认为，以异性恋为目标群体的研究和干预措施与生育力存在高度关联。基于Loseke的理论，可能的原因则是，中年人的性行为失去了"社会问题博弈" (social problem game)。研究和预防政策中存在的盲点也可能是因为不同发声者, 例如利益群体、政策制定者和政客之间就规范性达成了统一意见。 Resumen: Este artículo examina críticamente las bases de las estrategias de prevención suecas y los documentos de políticas que tienen que ver con los riesgos sexuales, e investiga en particular cómo los riesgos sexuales están representados con relación al grupo de individuos heterosexuales de mediana edad. Estas estrategias de prevención y documentos de políticas parecen estar escritos bajo el supuesto de que las relaciones sexuales están limitadas a la actividad sexual con individuos de la misma orientación sexual, edad, comportamiento o consumo de drogas, un supuesto que puede ser cuestionado. Hemos realizado una revisión del alcance de la investigación existente y hemos examinado las estrategias nacionales de prevención suecas, analizando los documentos de políticas sobre riesgos sexuales. Los resultados demuestran que hay una falta tanto de investigación como de intervenciones que tengan como objetivo a los heterosexuales de mediana edad. Argumentamos que la investigación e intervenciones para los heterosexuales tienen conexiones fuertes a la fertilidad. Basándose en la teorización de Loseke, la explicación podría ser que el comportamiento sexual en personas de mediana edad pierde el "juego del problema social." Los puntos ciegos que se observan en la investigación y políticas solo pueden ser explicados por un acuerdo en normatividad entre los diferentes creadores de reclamos, como los grupos de interés, creadores de políticas y políticos.